2010
DOI: 10.1002/tea.20372
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of teacher impact on student inquiry science performance using a hierarchical linear model

Abstract: Teachers play a central role in inquiry science classrooms. In this study, we investigate how seven teacher variables (i.e., gender, experience, perceived importance of inquiry and traditional teaching, workshop attendance, partner teacher, use of technology) affect student knowledge integration understanding of science topics drawing on previous research. Using a two‐level hierarchical linear model, we analyze year‐end knowledge integration performance of 4,513 students taught by 40 teachers across five state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 41 publications
2
37
1
2
Order By: Relevance
“…The Knowledge Integration (KI) perspective for interdisciplinary teaching emphasizes the role of teachers because it is their responsibility to encourage students to establish a successful conceptual change by integrating prior knowledge with new ideas and practices, which inevitably results in a more coherent understanding of science and math (Linn, 2006;Liu, Lee, & Linn, 2010). As a result, KI theory provides a rationale for the guiding mechanisms, which pertain to the acquisition, connection, and redefinition of the learner's knowledge under a constructivist view of learning (Bransford et al, 2000;Linn, 2006).…”
Section: Knowledge Integrationmentioning
confidence: 99%
“…The Knowledge Integration (KI) perspective for interdisciplinary teaching emphasizes the role of teachers because it is their responsibility to encourage students to establish a successful conceptual change by integrating prior knowledge with new ideas and practices, which inevitably results in a more coherent understanding of science and math (Linn, 2006;Liu, Lee, & Linn, 2010). As a result, KI theory provides a rationale for the guiding mechanisms, which pertain to the acquisition, connection, and redefinition of the learner's knowledge under a constructivist view of learning (Bransford et al, 2000;Linn, 2006).…”
Section: Knowledge Integrationmentioning
confidence: 99%
“…Sallee's (2011) dissertation findings showed that participants in schools categorized as "distinguished" were more likely to experience and implement the effective professional development described in such reports, suggesting a correlation between professional development and high student achievement. Likewise, Liu, Lee, and Linn (2010) found similar results generated from a study including forty teachers in five states and over 4,500 students in which "both workshop attendance and having a partner teacher had a positive impact on student science achievement" (p. 814).…”
Section: Professional Developmentsupporting
confidence: 57%
“…Inquiry science can be defined as science instruction that focuses on students developing questions, formulating hypothesis, designing and conducting investigations, and communicating their findings (NRC, 2000). Inquiry science is meant to be an authentic experience of the scientific process that mirrors the process conducted by professional scientists (Liu, Lee, & Linn, 2010;NRC, 2012).…”
Section: Science Pedagogy In the Ngssmentioning
confidence: 99%